Lesões no sistema nervoso central e na pele de cães com cinomose submetidos à necropsia na região central do Rio Grande do Sul, Brasil - Areco, Walter Vicente Cardozo (2021)
Canine distemper is a frequently fatal viral disease of dogs caused by canine distemper virus (CDV). Many aspects of canine distemper remain poorly understood. The aim of this study was to explore unusual or poorly described presentations of distemper in the literature. The first study of this thesis aimed to characterize the distribution and histopathological aspects of spinal cord injuries in dogs with spontaneous demyelinating leucoencephalomyelitis (DLEM) induced by CDV. Seventeen dogs with DLEM submitted to necropsy at the Laboratory of Veterinary Pathology at UFSM (2006-2008) were studied. Spinal cord sections were subjected to hematoxylin and eosin (H&E), Luxol Fast Blue and immunohistochemistry for CDV. Seventy-two of 231 spinal cord sections from these animals had histological lesions, which consistently affected the white matter. The lumbosacral region was mostly affected (13/17), followed by the thoracolumbar (11/17), cervical (9/17) and cervicothoracic (9/17). Lesions were most common in the lateral (42/72) and dorsal funiculi (31/72). Demyelination (17/17), astrocytosis (17/17), microgliosis (17/17), gemistocytes (11/17) and non-suppurative inflammation (10/17) were frequent in the white matter. Grey matter changes were less common, and included gliosis (8/17), non-suppurative inflammation (7/17) and malacia (5/17). Acute lesions were most prevalent (13/17) but it was common (10/17) for the same dog to have lesions at different stages of evolution in distinct spinal cord regions. Spinal cord lesions did not always correlate with the reported clinical signs and some dogs did not present spinal cord-related clinical signs. The second study aimed to characterize hyperkeratosis in the footpads, nasal planum and other skin regions in dogs naturally infected with CDV. Twelve dogs with canine distemper and concomitant cutaneous hyperkeratosis submitted to necropsy at the Laboratory of Veterinary Pathology at UFSM (2006-2018) were retrospectively investigated. Paraffin blocks were retrieved and new skin sections were stained with H&E and submitted to immunohistochemistry for CDV antigens. Twenty-three foci of hyperkeratosis were described, affecting footpads (11/12), nasal planum (4/12), periocular region (2/12), ventral abdomen (2/12), haired skin from the snout (2/12), scrotum (1/12) and vulva (1/12). Histopathological analysis was performed in 17 skins and revealed orthokeratotic hyperkeratosis in all cases, sometimes accompanied by other lesions, including: intracytoplasmic inclusions (14/17 skins analyzed), acanthosis (9/17), hydropic degeneration (6/17) and parakeratotic hyperkeratosis (4/17). Fifteen histological sections from 11 dogs were positive by immunohistochemistry. Labelling was most common in the epidermis, followed by sweat glands and endothelial cells/pericytes of dermal blood vessels. No differences in histopathological and immunohistochemical findings between skin from the nasodigital region and non-nasodigital areas were evidenced. The importance of recognizing cutaneous lesions in distemper is highlighted, thus contributing to the early diagnosis. This investigation has characterized poorly explored cutaneous and spinal cord lesions in dogs with distemper. We hope our findings will facilitate the clinicopathologic diagnosis of future cases of distemper and contribute to future pathogenesis studies.